Energy Storage: Highly Efficient Materials Assembly Via Electrophoretic Deposition for Electrochemical Energy Conversion and Storage Devices (Adv. Energy Mater. 7/2016). Issue 7 (April 2016) - Ye, Luhan; Wen, Kechun; Zhang, Zuoxiang; Yang, Fei; Liang, Yachun; Lv, Weiqiang; Lin, Yukun; Gu, Jianmin; Dickerson, James H.; He, Weidong
Abstract : In article number 1502018, Weidong He and co‐workers present the use of the electrophoretic deposition (EPD) technique for assembling an energy conversion/storage device to power the green world. The advantages of EPD in the assembly of nanomaterials for energy conversion/storage devices are unprecedented. As an efficient assembly technique, EPD simplifies the industrial process for realizing efficient configurations of supercapacitors, fuel cells and lithium batteries.